Conserved Functions of the MATE Transporter BIG EMBRYO1 in Regulation of Lateral Organ Size and Initiation Rate. Issue 8 (14th August 2015) - Suzuki, Masaharu; Sato, Yutaka; Wu, Shan; Kang, Byung-Ho; McCarty, Donald R.
Abstract : Big embryo 1 encodes a trans -Golgi localized MATE transporter required for regulation of lateral organ size and initiation rate in plants. Abstract: Genetic networks that determine rates of organ initiation and organ size are key regulators of plant architecture. Whereas several genes that influence the timing of lateral organ initiation have been identified, the regulatory pathways in which these genes operate are poorly understood. Here, we identify a class of genes implicated in regulation of the lateral organ initiation rate. Loss-of-function mutations in the MATE transporter encoded by maize ( Zea mays ) Big embryo 1 ( Bige1 ) cause accelerated leaf and root initiation as well as enlargement of the embryo scutellum. BIGE1 is localized to trans -Golgi, indicating a possible role in secretion of a signaling molecule. Interestingly, phenotypes of bige1 bear striking similarity to cyp78a mutants identified in diverse plant species. We show that a CYP78A gene is upregulated in bige1 mutant embryos, suggesting a role for BIGE1 in feedback regulation of a CYP78A pathway. We demonstrate that accelerated leaf formation and early flowering phenotypes conditioned by mutants of Arabidopsis thaliana   BIGE1 orthologs are complemented by maize Bige1, showing that the BIGE1 transporter has a conserved function in regulation of lateral organ initiation in plants. We propose that BIGE1 is required for transport of an intermediate or product associated with the CYP78A pathway.